Mitochondrially targeted tamoxifen in patients with metastatic solid tumours: an open-label, phase I/Ib single-centre trial - Bielcikova, Zuzana; Stursa, Jan; Krizova, Ludmila; Dong, Lanfeng; Spacek, Jan; Hlousek, Stanislav; Vocka, Michal; Rohlenova, Katerina; Bartosova, Olga; Cerny, Vladimir; Padrta, Tomas; Pesta, Michal; et al. (EClinicalMedicine, 2023)
BACKGROUND: Mitochondria present an emerging target for cancer treatment. We have investigated the effect of mitochondrially targeted tamoxifen (MitoTam), a first-in-class anti-cancer agent, in patients with solid metastatic tumours. METHODS: MitoTam was tested in an open-label, single-centre (Department of Oncology, General Faculty Hospital, Charles University, Czech Republic), phase I/Ib trial in metastatic patients with various malignancies and terminated oncological therapies. In total, 75 patients were enrolled between May 23, 2018 and July 22, 2020. Phase I evaluated escalating doses of MitoTam in two therapeutic regimens using the 3 + 3 design to establish drug safety and maximum tolerated dose (MTD). In phase Ib, three dosing regimens were applied over 8 and 6 weeks to evaluate long-term toxicity of MitoTam as the primary objective and its anti-cancer effect as a secondary objective. This trial was registered with the European Medicines Agency under EudraCT 2017-004441-25. FINDINGS: In total, 37 patients were enrolled into phase I and 38 into phase Ib. In phase I, the initial application of MitoTam via peripheral vein indicated high risk of thrombophlebitis, which was avoided by central vein administration. The highest dose with acceptable side effects was 5.0 mg/kg. The prevailing adverse effects (AEs) in phase I were neutropenia (30%), anaemia (30%) and fever/hyperthermia (30%), and in phase Ib fever/hyperthermia (58%) together with anaemia (26%) and neutropenia (16%). Serious AEs were mostly related to thromboembolic (TE) complications that affected 5% and 13% of patients in phase I and Ib, respectively. The only statistically significant AE related to MitoTam treatment was anaemia in phase Ib (p = 0.004). Of the tested regimens weekly dosing with 3.0 mg/kg for 6 weeks afforded the best safety profile with almost all being grade 1 (G1) AEs. Altogether, five fatalities occurred during the study, two of them meeting criteria for Suspected Unexpected Serious Adverse Events Reporting (SUSAR) (G4 thrombocytopenia and G5 stroke). MitoTam showed benefit evaluated as clinical benefit rate (CBR) in 37% patients with the largest effect in renal cell carcinoma (RCC) where four out of six patients reached disease stabilisation (SD), one reached partial response (PR) so that in total, five out of six (83%) patients showed CBR. INTERPRETATION: In this study, the MTD was established as 5.0 mg/kg and the recommended dose of MitoTam as 3.0 mg/kg given once per week via central vein with recommended preventive anti-coagulation therapy. The prevailing toxicity included haematological AEs, hyperthermia/fever and TE complications. One fatal stroke and non-fatal G4 thrombocytopenia were recorded. MitoTam showed high efficacy against RCC. FUNDING: Smart Brain Ltd. TRANSLATION: For the Czech translation of the abstract see Supplementary Materials section.
Keywords: Cancer; Phase I/Ib clinical trial; Renal cell carcinoma; Mitochondrially targeted tamoxifen